An assessment of place attachment in Melaka from tourists’ perspectives and ICT - Ab Rahman, Syakir Amir; Dura, Nur'Hidayah; Nik Mohd Adib, Nik Mohd Aizat; Azhari, Afzal; Yukihiro, Masuda (UPSI Press, 2020)
The rapid urban population growth worldwide has given rise to complex cities across the globe, particularly concerned with place attachment and digital technologies. In this new landscape, the emergence of smart devices is highly favorable to connect everyday infrastructures via the present networks available to create a sense of place. The concept of sense of place in heritage and culture is synonymous with Melaka as a famous heritage site which achieved recognition from UNESCO. However, when it comes to tourist behaviors, their place attachment, arrivals and purpose of visit highly influence their perceptions. Their priority in selecting Melaka as their holiday destination might differ based on several place attachment affective factors which are influenced by digital technologies. There are several problems to consider in order to improve place attachment in the study area, which are the prosperity of the tourism industry in Melaka threatening its own authenticity and the rapid modernization of the area dehumanizing its sense of place. Based on these factors, there is seemingly a conflict between the digital world and place attachment among the tourists in the study area. Therefore, the study aims to ascertain the concept of place attachment and determine the relationship between travel behavior (focusing only on trip frequency) and place attachment affective factors in response to digital technologies. By using ANOVA, the level of place attachment can be analyzed using data involving background of respondents, trip frequency and place attachment affective factors.